2013
DOI: 10.1371/journal.pone.0053916
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Risk of Colorectal Cancer: A Systematic Review of Prospective Studies

Abstract: BackgroundMounting evidence indicates that obesity may be associated with the risk of colorectal cancer (CRC). To conduct a systematic review of prospective studies assessing the association of obesity with the risk of CRC using meta-analysis.Methodology/Principal FindingsRelevant studies were identified by a search of MEDLINE and EMBASE databases before January 2012, with no restrictions. We also reviewed reference lists from retrieved articles. We included prospective studies that reported relative risk (RR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
378
3
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(417 citation statements)
references
References 69 publications
19
378
3
17
Order By: Relevance
“…BMI, on the other hand, showed negative correlation with some carcinoma-enriched MLGs. These results are in agreement with meta-analysis showing that central obesity is a more reliable risk factor for CRC than general obesity 27 . Consistent with a significant role played by diet, KEGG orthology (KO) modules for phosphotransferase systems, transporters for a number of different sugars, were overrepresented in healthy controls compared with adenoma samples or in adenoma compared with carcinoma samples (Fig.…”
Section: Resultssupporting
confidence: 92%
“…BMI, on the other hand, showed negative correlation with some carcinoma-enriched MLGs. These results are in agreement with meta-analysis showing that central obesity is a more reliable risk factor for CRC than general obesity 27 . Consistent with a significant role played by diet, KEGG orthology (KO) modules for phosphotransferase systems, transporters for a number of different sugars, were overrepresented in healthy controls compared with adenoma samples or in adenoma compared with carcinoma samples (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Obesity was found to increase the risk of colorectal cancer. Ma et al had conducted a systematic review on 54 studies assessing the association of obesity with the risk of colorectal cancer (Ma et al, 2013). They concluded that both of general obesity (measured using Body Mass Index) and central obesity (measured using waist circumference) were highly linked to the colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Five cohorts in men (2-6) and four in women (2,4,7,8) found positive associations between high versus low waist circumference and/or WHR and colon cancer risk, with summarized relative risks of 1.81 in men and 1.50 in women (9). A small number of studies (3-7) have suggested that measures of abdominal adiposity may be more predictive for colon cancer risk than BMI.…”
Section: Introductionmentioning
confidence: 99%